A Statistical Quality Control study on Corro-Coat Incorporated - Caballes, Christian Frederick; Rodriguez, Sharmaine; Telan, Romina (Diliman, Quezon City College of Engineering, 2003)
Corro Coat, Inc. is a sub-company of the D & L Industries manufacturing powder coatings. It contributes 70% in market share for the said product. Its major product is the MX Series, which comprises 75% of the total production of the company. The company?s customer is the Concepcion-Carrier Air Conditioning. The focus of the study is on the said major product line. Analyses were performed using different statistical quality control and problem analysis tools. Using the Pareto Chart, the three prevailing problems that caused rejection were determined. These are Gloss problem, Off Shading and the Presence of Specks. For the said problems affecting the quality characteristics of the coating, Statistical Process Control (SPC) Analysis was performed. X and R Chart were used for the Gloss Problem; X and Rm, for the Off Shades and C Chart for the Presence Specks. The control charts for the Gloss Problem at 60⁰, off shades and presence of specks are both in control, only that there are shifts during the process but not enough to cause the process to be out of control. The control charts for the Gloss at 20⁰ are out of control. These were revised for new control limits for future operations. Process Capability Analyses were also performed for each characteristic. The process capability index for the gloss at 60⁰ is 0.72615. This means that the process is incapable. Its potential capability is 1.8329 and the specification band used is 54.558%. For the gloss at 20⁰, the capability index is 1.7117. The process is capable in this aspect. For the off-color the index is 1.272, also, process is capable. For the attribute capability for the specks, the index is 0.6497, signaling that the process is incapable. Quality Control Analysis was also performed and the total cost for each characteristic are: P(7802 + 400x) for the gloss characteristic where x is the number of units inspected. The total cost consists of appraisal and internal failure costs. For the specks, P(7802 + 42x) and the off shade, P(8697.208+430x). Acceptance Sampling Analysis conducted by the group showed that the current technique used by the company must be continued since it yielded high probability of acceptance and low Acceptable Outgoing Quality (AOQ). The values are: for the Specks, probability of Acceptance, Pa is 0.979 and AOQ is 0.00465; for the Off Shade, P is 0.973 and AOQ is 0.00613 and lastly, for the Gloss, Pa is 0.98597 and AOQ of 0.00324. Having done all these analyses, the group generated recommends reduction of assignable causes through continuous reviews of quality improvement team and the implementation further the quality system by maximizing the factors that caused rejections.
Feasibility study
Keywords: Corro-coat Incorporated; Coatings; Quality control